Personality, behavioral strengths and difficulties and performance of adolescents with high achievements in science, literature, art and sports - Papageorgiou, K. A.; Likhanov, M.; Costantini, G.; Tsigeman, E.; Zaleshin, M.; Budakova, A.; Kovas, Y. (Personality and Individual Differences, 2020)
Highlights